2012
DOI: 10.1158/0008-5472.can-12-2359
|View full text |Cite|
|
Sign up to set email alerts
|

Host Immune Defense Peptide LL-37 Activates Caspase-Independent Apoptosis and Suppresses Colon Cancer

Abstract: Cathelicidins are a family of bacteriocidal polypeptides secreted by macrophages and polymorphonuclear leukocytes (PMN). LL-37, the only human cathelicidin, has been implicated in tumorigenesis, but there has been limited investigation of its expression and function in cancer. Here, we report that LL-37 activates a p53-mediated, caspase-independent apoptotic cascade that contributes to suppression of colon cancer. LL-37 was expressed strongly in normal colon mucosa but downregulated in colon cancer tissues, wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
117
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(125 citation statements)
references
References 43 publications
5
117
2
1
Order By: Relevance
“…4A) [14]. FK-16, a fragment of residues 17 to 32 of LL-37, upregulated the expression of LC3-I/II, Atg5 and Atg7, enabling formation of LC3-positive autophagosomes [15]. These observations show that FK-16 triggers caspase-independent apoptosis and autophagy through the p53-Bcl-2/Bax signaling in colon cancer cells (Fig.…”
Section: Anti-cancer Effectsmentioning
confidence: 64%
“…4A) [14]. FK-16, a fragment of residues 17 to 32 of LL-37, upregulated the expression of LC3-I/II, Atg5 and Atg7, enabling formation of LC3-positive autophagosomes [15]. These observations show that FK-16 triggers caspase-independent apoptosis and autophagy through the p53-Bcl-2/Bax signaling in colon cancer cells (Fig.…”
Section: Anti-cancer Effectsmentioning
confidence: 64%
“…They showed that the expression of LL37 was remarkably downregulated in human colon cancer tissues, whereas exogenous LL37 induced apoptotic cell death in cultured colon cancer cells. 1,2 However, LL37 strongly reduced cell viability at high doses (20-60 μmol/L), and it did not show any effect at low doses (0.5-10 μmol/L) or even stimulate cell proliferation in other cancer types. 1 The combination of LL37 and an anticancer chemotherapy drug was considered to achieve higher antitumor efficacy and minimize the emergence of resistance.…”
Section: Introductionmentioning
confidence: 94%
“…1,2 However, LL37 strongly reduced cell viability at high doses (20-60 μmol/L), and it did not show any effect at low doses (0.5-10 μmol/L) or even stimulate cell proliferation in other cancer types. 1 The combination of LL37 and an anticancer chemotherapy drug was considered to achieve higher antitumor efficacy and minimize the emergence of resistance. Docetaxel (Doc), a semisynthetic analog of paclitaxel, is a widely used anticancer agent that has been used for the treatment of various human malignancies.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Entre seus efeitos no sistema imune, elas participam da secreção de citocinas por macrófagos murinos (Pinheiro da Silva et al, 2009a), alteram respostas quimiotáticas (Yang et al, 2000b), apoptose (Ren et al, 2012) ativação de inflamassoma (Salzer et al, 2014) e fagocitose (Wang et al, 2014 Barlow et al, 2011), como também por impedir a sinalização do complexo receptor/ligante em células dendríticas e macrófagos (Di Nardo et al,2007;Brown et al, 2011). Isso resultaria em menor produção de citocinas quando LPS e LL-37 estão presentes simultaneamente.…”
Section: Peptídeos Antimicrobianosunclassified